Causes of mortality of kiwi (Apteryx spp.) in New Zealand: a retrospective analysis of post-mortem records, 2010–2020. Issue 2 (4th March 2023) - Gulliver, EL; Hunter, SA; Vallee, E; Castillo-Alcala, F
ABSTRACT: Aims: To examine and assess causes of mortality of kiwi ( Apteryx spp.) submitted to Massey University between 2010 and 2020 across the five recognised species according to location, age group and captivity status in New Zealand. Methods: Post-mortem reports were obtained from the Massey University/Te Kunenga ki Pūrehuroa School of Veterinary Science/Wildbase Pathology Register. Inclusion criteria were all species of kiwi with a date of post-mortem examination between August 2010 and August 2020. Data from each report was exported, categorised and compared using Microsoft Excel. Results: Of a total of 1, 005 post-mortem reports, there were 766 North Island brown kiwi (NIBK; A. mantelli ), 83 tokoeka ( A. australis ), 73 rowi ( A. rowi ), 49 great spotted kiwi ( A. haastii ), and 34 little spotted kiwi ( A. owenii ). This comprised 19 eggs/embryos, 125 neonatal, 473 juvenile, 153 subadult, and 235 adult kiwi. There were 615 kiwi from wild populations, 148 from sanctuary populations, 238 from captivity, and four from unspecified locations. The leading cause of death was trauma, affecting 322 (32.0 (95% CI = 29.2–35.0)%) kiwi including 289 (37.3 (95% CI = 26.0–31.7)%) NIBK. Nearly half of these died from predation by mustelids, with losses recorded from neonates to adults and clustered in the central to southern North Island. Predation by dogs was the second most common cause of death, killing 84 (8.4 (95% CI = 6.7–10.2)%) kiwi, of which 65.5% came from the northern districts of the North Island. Non-infectious disease killed 214 (21 (95% CI = 18.8–24.0)%) kiwi, and included developmental deformities, gastrointestinal foreign bodies and predator trap injuries. Infectious disease killed 181 (18.0 (95% CI = 15.7–20.5)%) kiwi and the proportion decreased with age, with common diagnoses including coccidiosis, bacterial septicaemia, avian malaria, and fungal respiratory disease. Starvation affected 42 (4.2 (95% CI = 3.0–5.6)%) kiwi, comprised of mainly neonatal or juvenile individuals from wild or sanctuary populations, with a higher percentage seen in tokoeka (11/83; 13.3%) compared to other species (min 0%, max 5.9%). The cause of death was undetermined in 246 (24.5 (95% CI = 21.8–27.3)%) cases, which was most often due to poor preservation of remains. This included 33/73 (46%) rowi and 32/83 (39%) tokoeka, and affected mainly birds from sanctuary and wild populations. Conclusions: This study enhances our understanding of causes of mortality in captive, wild and sanctuary populations of all kiwi species and age groups within contemporary New Zealand.